Cyberbullying Victimization and Adolescent Drinking Behavior: Deviant Peer Affiliation as a Mediator and Personal Growth Initiative as a Moderator - Chen, Pei; Xin, Mucheng; Xie, Qi; Wei, Chang; Yu, Chengfu; Gan, Xiong; Xie, Xiaodong; Zhang, Wei (Frontiers in Psychiatry, 2020)
Research has demonstrated a robust positive association between cyberbullying victimization and adolescent drinking behavior; however, the mediating and moderating mechanisms underlying this relationship remain largely unexplored. Grounded in the social development model and person-environment interactions model, our study explored whether deviant peer affiliation mediated the relationship between cyberbullying victimization and adolescent drinking behavior and whether this mediating effect was moderated by personal growth initiative. A sample of 1,006 adolescents (Mage = 13.16 years; SD = 0.67) anonymously completed self-report questionnaires. Structural equation modeling indicated that the positive association between cyberbullying victimization and drinking behavior was partly mediated by deviant peer affiliation for both girls and boys. Further, this mediating process was stronger for adolescents with low personal growth initiative than for those with high personal growth initiative. There were no significant gender differences for this moderating effect. These findings underline the importance of deviant peer affiliation and personal growth initiative in understanding how and when cyberbullying victimization impacts adolescent drinking behavior.